ATAC-pipe: general analysis of genome-wide chromatin accessibility. (11th June 2019) - Zuo, Zuqi; Jin, Yonghao; Zhang, Wen; Lu, Yichen; Li, Bin; Qu, Kun
Abstract: Assay of Transposase-Accessible Chromatin by deep sequencing (ATAC-seq) has been widely used to profile the chromatin accessibility genome-wide. For the absence of an integrated scheme for deep data mining of specific biological issues, here we present ATAC-pipe, an efficient pipeline for general analysis of chromatin accessibility data obtained from ATAC-seq experiments. ATAC-pipe captures information includes not only the quality of original data and genome-wide chromatin accessibility but also signatures of significant differential peaks, transcription factor (TF) occupancy and nucleosome positions around regulatory sites. In addition, ATAC-pipe automatically converts statistic results into intuitive plots at publication quality, such as the read length distribution, heatmaps of sample clustering and cell-type-specific regulatory elements, enriched TF occupancy with motifs footprints and TF-driven regulatory networks. ATAC-pipe provides convenient workflow for researchers to study chromatin accessibility and gene regulation. Availability https://github.com/QuKunLab/ATAC-pipe